Women’s Empowerment in Gender Verses in the Surah al-Nisā' - Baihaqi, Yusuf (Faculty of Ushuluddin and Religious Study, Universitas Islam Negeri Raden Intan Lampung, 2023)
The content of Surah al-Nisāʼ in the Qur'an is full of messages regarding the importance of empowering women. However, many Muslim communities still underestimate and marginalize women, rendering them less empowered. This research describes women's empowerment in Islam and moderate interpretations of Qur'anic verses related to women. It analyzes the verses about women empowerment in Surah al-Nisāʼof the Quran, referring to several fair interpretations and linking them to field phenomena. The results show that the Qur'an is a holy book that supports women's empowerment, an aspect perceived to have social, economic, health, spiritual, and legal dimensions in Surah al-Nisāʼ. It is urgent to empower women to live worthy and equal to men. This research is expected to help understand the verses on moderate women’s empowerment equally and justly as men in building a civilization on earth.